ASESMEN POTENSI TSUNAMI DAN KESIAPSIAGAAN MASYARAKAT PESISIR: STUDI KASUS TELUK ULEE LHEUE, ACEH BESAR - Benazir Benazir; Syamsidik Syamsidik; Yunita Idris (JURNAL TEKNIK HIDRAULIK, 2022)
The 2004 Indian Ocean Tsunami, which devastated the coasts of Aceh and Nias, revealed that the event was a mega-hazard category. Following the disaster, a new era in the development of tsunami mitigation throughout the archipelago began. Nonetheless, given the impact of the two tsunamis that occurred at the end of 2018, achieving mitigation within 17 years poses a unique challenge and high priority. The relationship between tsunami-prone areas and community preparedness has become a crucial factor in achieving regional disaster resilience. The objective of this research is to provide a regional assessment of tsunamis risk as well as community preparedness for future tsunami. The coast of Teluk Ulee Lheue, Aceh Besar, was chosen as the location for the assessment as a role model. The research method consists of tsunami mathematical modeling considering the impact caused by the magnitude of earthquakes 8.2, 9.15, and 9.2. The Nonlinear Shallow Water Equation (NSWE) model was used in the simulation, which was discretized using the explicit leap-frog Finite Difference Method. Field activities were included not only to collect topography and land use data but also to gather information and community response. The data was provided directly from the local community through the completion of a questionnaire, with a total of 150 respondents being evaluated. The findings of this study reveal that the consequences of the tsunami inundation remain quite considerable, even for a smaller-scale earthquake than the previous 2004 event. In general, the degree of community preparedness seems to be quite high, especially in terms of tsunami awareness. An improvement in disaster emergencies is required, specifically in the household sector. However, with a high degree of community preparedness, it would be essential to carry out individual evacuations rapidly. Keywords: tsunami hydrodynamics, numerical simulation, run-up, community preparedness, environmental social